2011
DOI: 10.1159/000328634
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Recruitment during Multiple Donor Platelet Apheresis Differs between Cell Separators

Abstract: Background: Recruitment of platelets (PLT) during donor PLT apheresis may facilitate the harvest of multiple units within a single donation. Methods: We compared two PLT apheresis procedures (Amicus and Trima Accel) in a prospective, randomized, paired cross-over study in 60 donors. The 120 donations were compared for depletion of circulating PLT in the donors, PLT yields and PLT recruitment. A recruitment was defined as ratio of total PLT yield and donor PLT depletion > 1. Results: Despite comparable differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
3
11
2
Order By: Relevance
“…Our data may theoretically not exclude a potential systematic underestimation of the effective donor blood volume, but we consider an underestimation in the order of one‐third from the formula of Nadler and Allen used in the Trima Accel very unlikely 13 . The observation of a significant increase of the mean PLT volume during plateletpheresis in PLT donors 5 also supports the hypothesis of a release of PLT in the circulation from an extravascular site. The origin of the PLT recruited is not primarily addressed by our study, but this aspect does not affect the development of a plateletpheresis prediction algorithm for healthy PLT donors.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our data may theoretically not exclude a potential systematic underestimation of the effective donor blood volume, but we consider an underestimation in the order of one‐third from the formula of Nadler and Allen used in the Trima Accel very unlikely 13 . The observation of a significant increase of the mean PLT volume during plateletpheresis in PLT donors 5 also supports the hypothesis of a release of PLT in the circulation from an extravascular site. The origin of the PLT recruited is not primarily addressed by our study, but this aspect does not affect the development of a plateletpheresis prediction algorithm for healthy PLT donors.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, our observations in a previous study have also suggested an increase of circulating white blood cells (WBCs) in the donors at the end of plateletpheresis 5 . This may be related to an unknown common mechanism recruiting blood cells in general during apheresis or to the accumulation of WBCs in the extracorporeal system during the procedure, followed by their return to the donor at the end of the procedure.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…On the other hand, platelet activation could be dependent in part in the apheresis equipment used. Bueno et al (2005) [44] reported that the in vitro activation of platelets can vary, depending on the centrifugation rotor and the re-suspension method.…”
Section: Discussionmentioning
confidence: 99%